Effects of Treatment of Paroxetine, Bupropion and Agomelatine on Feeding and Weight Change in Female Rats - Ulker, Nazife; Yardimci, Ahmet; Ozdemir, Gokcen; Bulmus, Ozgur; Ozcan, Mete; Canpolat, Sinan; Kelestimur, Haluk (Wiley, 2015)
[Abstract Not Available]